2008
DOI: 10.1111/j.1525-1314.2008.00795.x
|View full text |Cite
|
Sign up to set email alerts
|

Aragonite and magnesite in eclogites from the Jæren nappe, SW Norway: disequilibrium in the system CaCO3–MgCO3 and petrological implications

Abstract: Eclogites from the Jaeren nappe in the Caledonian orogenic belt of SW Norway contain aragonite, magnesite and dolomite in quartz-rich layers. The carbonates comprise composite grains that occur interstitially between phases of the eclogite facies assemblage: garnet + omphacite + zoisite + clinozoisite + quartz + apatite + rutile ± dolomite ± kyanite ± phengite. Pressure and temperature conditions for the main eclogite stage are estimated to be 2.3-2.8 GPa and 585-655°C. Published ultrahigh pressure (UHP) exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 83 publications
(140 reference statements)
1
13
0
1
Order By: Relevance
“…6 from this study closely resemble Fig. 7a in Smit et al (2008), and that Fig. 10B from this study apparently resemble Fig.…”
Section: Metamorphic Conditions and Evolutionsupporting
confidence: 75%
See 1 more Smart Citation
“…6 from this study closely resemble Fig. 7a in Smit et al (2008), and that Fig. 10B from this study apparently resemble Fig.…”
Section: Metamorphic Conditions and Evolutionsupporting
confidence: 75%
“…10B from this study apparently resemble Fig. 10 in Smit et al (2008) with the exception that aragonite is present in the Garbon eclogites of Norway but calcite crosscuts magnesite in our studied Tso Morari eclogite and that goethite formed always alongside the first generation of calcite (Point 3 in Fig. 6 and Table 1).…”
Section: Metamorphic Conditions and Evolutionmentioning
confidence: 55%
“…1b), which hosts an eclogite occurrence that is somewhat enigmatic in the context of recent geodynamic models. Recently, Lu-Hf dating of garnet from sporadic eclogite outcrops yielded an age of 471 AE 1 Ma, which was interpreted to closely approximate the time when peak-metamorphic conditions of c. 2.6 GPa and 585-655 8C were reached (Smit et al 2008(Smit et al , 2010. The data showed that HP metamorphism was protracted, lasting at least until c. 458 Ma.…”
Section: The Jaeren Areamentioning
confidence: 92%
“…Aragonite and magnesite present clear disequilibrium textures, indicating the replacement of magnesite by aragonite (Smit et al, 2008). They are inferred to have occurred via a coupled dissolution/precipitation reaction not related to the breakdown of dolomite.…”
Section: Introductionmentioning
confidence: 96%
“…Aragonite inclusions in diamond have recently been interpreted as evidence of very deep subductions of roughly 280 km (Dobrzhinetskaya et al, 2006) although P-T conditions for the main eclogite stage in the eclogites from the relevant Jaeren nappe in the Norwegian Caledonian orogenic belt, have been estimated at 2.3-2.8 GPa and 585-655 C (Smit et al, 2008). Aragonite and magnesite present clear disequilibrium textures, indicating the replacement of magnesite by aragonite (Smit et al, 2008).…”
Section: Introductionmentioning
confidence: 99%